2013
DOI: 10.1098/rspb.2012.2336
|View full text |Cite
|
Sign up to set email alerts
|

Mimetic host shifts in an endangered social parasite of ants

Abstract: An emerging problem in conservation is whether listed morpho-species with broad distributions, yet specialized lifestyles, consist of more than one cryptic species or functionally distinct forms that have different ecological requirements. We describe extreme regional divergence within an iconic endangered butterfly, whose socially parasitic young stages use non-visual, non-tactile cues to infiltrate and supplant the brood in ant societies. Although indistinguishable morphologically or when using current mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 41 publications
2
41
0
1
Order By: Relevance
“…The cuckoo strategy requires more perfect mimicry, i.e. precise adaptation to the specific host ant (Thomas et al 2015). Accurate local adaptation in the cuckoo M. alcon would lead to an even higher level of differentiation among the populations than genetic drift would do alone.…”
Section: Discussionmentioning
confidence: 99%
“…The cuckoo strategy requires more perfect mimicry, i.e. precise adaptation to the specific host ant (Thomas et al 2015). Accurate local adaptation in the cuckoo M. alcon would lead to an even higher level of differentiation among the populations than genetic drift would do alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the host specificity pattern observed in M. rebeli and M. alcon is extremely complex, as a consequence of local adaptations. For instance, studies on M. rebeli from the Pyrenees show that its populations restrictively exploit colonies of M. schencki Emery, 1894 while eastern M. rebeli populations (mainly in Poland) use both M. sabuleti Meinert, 1861 and M. scabrinodis Nylander, 1846 (Thomas et al 2005b(Thomas et al , 2013. Thomas et al (2013) have more recently suggested that this host shift could be a trace of a major difference in chemical profiles, enabling each social parasite to infiltrate and exploit even very different Myrmica host societies.…”
Section: Host Ants' Diversification In Maculinea Populationsmentioning
confidence: 99%
“…In contrast, recent studies have shown a high degree of physiological specialisation of Maculinea species to their hosts, making it locally impossible to infiltrate and exploit non-host colonies (Thomas et al 1989;Akino et al 1999;Schönrogge et al 2004;Thomas et al 2005). This specialisation, in principle, should make each butterfly species incompatible with Myrmica species considerably differing in physiology and social behaviour from their own host species (Thomas et al 2012), thus also being expressed in higher niche overlap scores. However, physiological specialisation is not addressed by our niche overlap measures only taking the Grinnellian niche space into account (Peterson et al 2011).…”
Section: Discussionmentioning
confidence: 85%